Free scholarships for TVET students to continue studies in China - Mimi Rabita, Abd Wahit (UMPSA, 2024)
MELAKA, 16 January 2024 - Malaysia-China collaboration within the framework of the Belt and Road Initiative benefits students when the Chinese government offers free scholarships to 1,000 Technical and Vocational Education and Training (TVET) students in the country to take courses there.